2019
DOI: 10.3389/fnsys.2018.00067
|View full text |Cite
|
Sign up to set email alerts
|

Locus Coeruleus Optogenetic Light Activation Induces Long-Term Potentiation of Perforant Path Population Spike Amplitude in Rat Dentate Gyrus

Abstract: Norepinephrine (NE) in dentate gyrus (DG) produces NE-dependent long-term potentiation (NE-LTP) of the perforant path-evoked potential population spike both in vitro and in vivo. Chemical activators infused near locus coeruleus (LC), the source of DG NE, produce a NE-LTP that is associative, i.e., requires concurrent pairing with perforant path (PP) input. Here, we ask if LC optogenetic stimulation that allows us to activate only LC neurons can induce NE-LTP in DG. We use an adeno-associated viral vector conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 73 publications
3
26
0
Order By: Relevance
“…We found that LC unit recording is feasible following manipulations to induce DREADD expression although the yield is relatively low as we were only able to perform successful electrophysiological recordings in 35% of the animals. This is similar to other research groups targeting locus coeruleus with success rates around 45% and is possibly due to the small size and location of the nucleus in the pontine brainstem (Quinlan et al, 2019). In the current experimental setting, we were not able to draw conclusions on the feasibility to chemogenetically increase LC neuronal activity with clozapine.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found that LC unit recording is feasible following manipulations to induce DREADD expression although the yield is relatively low as we were only able to perform successful electrophysiological recordings in 35% of the animals. This is similar to other research groups targeting locus coeruleus with success rates around 45% and is possibly due to the small size and location of the nucleus in the pontine brainstem (Quinlan et al, 2019). In the current experimental setting, we were not able to draw conclusions on the feasibility to chemogenetically increase LC neuronal activity with clozapine.…”
Section: Discussionsupporting
confidence: 79%
“…An alternative for increasing transduction efficiency and selectivity is the use of a Cre-Lox system for hM3Dq expression in LC (Witten et al, 2011). The group of Harley and Walling et al used a TH:Cre rat line to induce expression of an opsin in LC by injecting a Cre-dependent AAV with the promoter and gene of interest between loxP sites, assuring selective expression in LC cells that contain Cre recombinase (Quinlan et al, 2019). Because of these findings we believe that for further optimization of the experimental approach studied in this work, transduction efficiency studies with different viral vector serotypes is required when targeting a new brain structure such as a brainstem nucleus, even when a similar type of neurons i.e., noradrenergic neurons are the primary content of the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Although the LC is limited in size (~3mm caudorostrally) and buried deep within the brainstem [78,79], several studies have successfully recorded from single neurons in LC of the macaque [26,27,[80][81][82][83][84]. In addition, LC can be activated using optogenetics [85][86][87][88], electrical microstimulation [14,16,58], and pharmacological manipulations [17,89,90]. Thus, it should be possible to alter the course of slow drift in the cortex using some, if not all, of these methods.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedure was carried out following appropriate sterilization. A hole was drilled in the skull (12.3-mm posterior and 1.3-mm left lateral to bregma) and an optrode, assembled just before the experiment (400-μm glass optical fiber; Thorlabs Inc), bundled with a 200/280-μm tungsten electrode; FHC), was lowered down at a 20° angle to 6.1–6.9-mm ventral to brain surface until LC neurons were identified by slow spontaneous spiking and burst response to toe pinch (audio-monitor and oscilloscope response; Quinlan et al. 2018 ).…”
Section: Methodsmentioning
confidence: 99%